2007
DOI: 10.1124/mol.106.033035
|View full text |Cite
|
Sign up to set email alerts
|

The α1b-Adrenoceptor Exists as a Higher-Order Oligomer: Effective Oligomerization Is Required for Receptor Maturation, Surface Delivery, and Function

Abstract: Approaches to identify G protein-coupled receptor oligomers rather than dimers have been lacking. Using concatamers of fluorescent proteins, we established conditions to monitor sequential three-color fluorescence resonance energy transfer (3-FRET) and used these to detect oligomeric complexes of the ␣ 1b -adrenoceptor in single living cells. Mutation of putative key hydrophobic residues in transmembrane domains I and IV resulted in substantial reduction of sequential 3-FRET and was associated with lack of pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
138
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 37 publications
10
138
0
Order By: Relevance
“…If this is also the case for the full-length mGluR at the cell surface, this could lead to an alternative and maybe more complex activation mechanism. Indeed, higher order oligomers have been observed recently for rhodopsin (41) and ␣-adrenergic receptors (42). Here, using fluorophore-labeled antibodies, we have shown that no significant FRET could be measured between mGluR dimers, whereas a high FRET signal was measured between the subunits within a dimer.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…If this is also the case for the full-length mGluR at the cell surface, this could lead to an alternative and maybe more complex activation mechanism. Indeed, higher order oligomers have been observed recently for rhodopsin (41) and ␣-adrenergic receptors (42). Here, using fluorophore-labeled antibodies, we have shown that no significant FRET could be measured between mGluR dimers, whereas a high FRET signal was measured between the subunits within a dimer.…”
Section: Discussionmentioning
confidence: 71%
“…mGlu5 Is a Dimer, Not a Higher Order Oligomer-At least some GPCRs may form not only dimers, but also higher order oligomers (41,42). If this occurs also for mGluRs, this would substantially complicate our analysis of their intramolecular signal transduction.…”
Section: Resultsmentioning
confidence: 99%
“…Mouse lines, treatment protocols, behavioural studies, dissections, and primary neuronal cultures, approved by Institutional Use and Care Committees, have been previously described 8,9 . Protocols used for FISH 8 , binding assays 8 , real-time PCR 8 , FRET 17 and co-immunoprecipitation 17 were performed as previously described or with minor modifications. Epitope tagged, BRET 2 , FRET and chimera receptor constructs were generated using standard cloning techniques and were confirmed by sequencing.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have demonstrated that some GPCRs belonging to the same sequence classes can form dimers 16 or, potentially, higher-order oligomers 17 . Although the 2AR and mGluR2 belong to different GPCR classes, we established the existence of 2AR/mGluR2 heterocomplexes by several methods: co-immunoprecipitation of human brain cortex samples (Fig.…”
mentioning
confidence: 99%
“…Although the GnRH receptor was one of the very first GPCRs shown to oligomerize at the PM as part of normal receptor function (Conn et al, 1982;Cornea et al, 2001), oligomerization in the ER-Golgi complex at the time of nascent protein synthesis and routing to the cell surface is a relatively new concept for GPCRs and suggests that there may also be a function for oligomerization at that early stage (Lee et al, 2000;Lopez-Gimenez et al, 2007;Pin et al, 2007). Perhaps oligomerization of two or more receptors acts to hide exposed hydrophobic surfaces or ER retention motifs that would otherwise signal an improperly folded receptor and be recognized as such by the quality control apparatus of the cell.…”
Section: The Dominant-negative Effect and Receptor Rescuementioning
confidence: 99%